THE ROLE OF TQM AND ORGANIZATIONAL CULTURE ON OPERATIONAL PERFORMANCE - Tanjoyo, Catherine; Harianto, Eric; Sutrisno, Timotius Febry Christian W. (Jurnal Aplikasi Manajemen, 2021)
TQM is one of the essential factors in organizational activities. This research aims to determine how TQM elements and organizational culture can lead to operational performance in a mineral water manufacturer in Pasuruan, East Java, Indonesia. Aside from that, researchers also measure how TQM elements, organizational culture, and operational performance can affect corporate performance. The respondents are 50 people from staff, suppliers, and consumers of the manufacturer. The method used in this research is a quantitative method that uses path analysis. The results showed that there is a significant impact between soft TQM elements towards operational performance. The results also showed a significant effect between hard TQM elements, organizational culture, and operational performance towards corporate performance. This research differs from other studies because the model analysis correlates organizational culture with TQM elements in a mineral water company.